Academic Writing Challenges and Supports: Perspectives of International Doctoral Students and Their Supervisors - Gupta, Shikha; Jaiswal, Atul; Paramasivam, Abinethaa; Kotecha, Jyoti (Frontiers in Education, 2022)
Introduction: Academic writing is a core element of a successful graduate program, especially at the doctoral level. Graduate students are expected to write in a scholarly manner for their thesis and scholarly publications. However, in some cases, limited or no specific training on academic writing is provided to them to do this effectively. As a result, many graduate students, especially those having English as an Additional Language (EAL), face significant challenges in scholarly writing. Further, academic mentors often feel burdened by reviewing and editing multiple drafts and find it difficult to help and support EAL students in the process of scientific writing. In this study, we explored academic writing challenges faced by EAL doctoral students and faculty supervisors at a research intensive post-secondary university in Canada. Methods and Analysis: We conducted a sequential explanatory mixed-method study using an online survey and subsequent focus group discussions with EAL doctoral students (n= 114) and faculty supervisors (n= 31). A cross-sectional online survey was designed and disseminated to the potential study participants using internal communications systems of the university. The survey was designed using a digital software called QualtricsTM. Following the survey, four FGDs were held, two each with two groups of our participants with an aim to achieve data saturation. The FGD guide was informed by the preliminary findings of the survey data. Quantitative data was analyzed using Statistical Package of Social Sciences (SPSS) and qualitative data was managed and analyzed using NVivo. Discussion: The study findings suggest that academic writing should be integrated into the formal training of doctoral graduate students from the beginning of the program. Both students and faculty members shared that discipline-specific training is required to ensure success in academic writing, which can be provided in the form of a formal course specifically designed for doctoral students wherein discipline-specific support is provided from faculty supervisors and editing support is provided from English language experts. Ethics and Dissemination: The general research ethics board of the university approved the study (#6024751). The findings are disseminated with relevant stakeholders at the university and beyond using scientific presentations and publications.